Adverse childhood experiences (ACEs) and substance use disorder (SUD): A scoping review - Leza, Leire; Siria, Sandra; López-Goñi, José J.; Fernández-Montalvo, Javier (Drug and alcohol dependence, 2021)
•ACE are prevalent among people with substance addiction problems.•There is a positive association between ACEs and a later diagnosis of SUD.•It is necessary to standardize criteria for evaluating ACE and SUD.•It is needed to clarify the mechanism of the relationship between ACE and SUD.•Prevention policies and specific training for professionals are needed. The long-term negative effects of adverse childhood experiences (ACEs) and their impact on physical and mental health has been widely studied. However, research about the relationship between ACEs and substance use disorder (SUD) diagnosis in adolescence and adulthood is still scarce. Therefore, this scoping review was conducted to collect the existing research findings to explore the relationship between the experience of ACEs and the diagnosis of SUD later in life. The PsycINFO, Medline, Scopus, Web of Science, and Cochrane Library databases were searched. After identifying the records based on eligibility and exclusion criteria, 12 studies were finally selected for inclusion. Most of the studies were conducted in the USA with adult male and female participants. All studies were cross-sectional in nature and assessed ACEs retrospectively. The main conclusions of the studies were that there is a higher prevalence of ACEs in the population with SUD than in the general population, and a positive association between ACEs and the development and severity of SUD in adolescence and adulthood. It is difficult to make comparisons between studies and to draw solid conclusions because of the lack of standardized criteria for evaluating ACEs and due to the heterogeneity in the substance types examined. More research is needed to fully elucidate the underlying mechanism of the relationship between ACEs and SUD.